Cognitive Impairment in Marginally Housed Youth: Prevalence and Risk Factors - Kristina Waclawik; Andrea A. Jones; Skye P. Barbic; Skye P. Barbic; Skye P. Barbic; Skye P. Barbic; Kristina M. Gicas; Tiffany A. O'Connor; Geoffrey N. Smith; Olga Leonova; Steve Mathias; Steve Mathias; et al. (Frontiers Media S.A., 2019)
Objective: Homeless and marginally housed youth are particularly vulnerable members of society, and are known to experience numerous health problems, including psychiatric illness, substance use, and viral infection. Despite the presence of these risk factors for cognitive compromise, there is limited research on the cognitive functioning of homeless and marginally housed youth. The present study examines the degree and pattern of cognitive impairment and associations with key risk factors in a sample of marginally housed young adults.Method: Participants (N = 101) aged 20-29 years old were recruited from single-room occupancy hotels, and underwent cognitive, psychiatric, neurological, and serological assessments.Results: Forty percent of participants were identified as mildly cognitively impaired across multiple domains, and 16% were moderately-severely impaired. Deficits in memory and attention were most prevalent, while impairments in inhibitory control/processing speed and cognitive flexibility were also present but tended to be less severe. Developmental and historical factors (premorbid intellectual functioning, neurological soft signs, earlier exposure to and longer duration of homelessness or marginal housing), as well as current health risks (stimulant dependence and hepatitis C exposure), were associated with cognitive impairment.Conclusions: The strikingly high rate of cognitive impairment in marginally housed young adults represents a major public health concern and is likely to pose a significant barrier to treatment and rehabilitation. These results suggest that the pathway to cognitive impairment involves both developmental vulnerability and modifiable risk factors. This study highlights the need for early interventions that address cognitive impairment and risk factors in marginalized young people.